The Effect of Plant Source on the Properties of Lignin-Based Polyurethanes - Lang, Jason M.; Shrestha, Umesh M.; Dadmun, Mark (Frontiers in Energy Research, 2018)
This work increases our understanding of the effect of plant source on the mechanical and morphological properties of lignin-based polyurethanes. Lignin is a polymer that is synthesized inside the plant cell wall and can be used as a polyol to synthesize polyurethanes. The specific aromatic structure of the lignin is heavily reliant on the plant source from which it is extracted. These results show that the mechanical properties of lignin-based polyurethanes differ based on lignin’s plant source. The morphology of lignin-based polyurethanes was examined using atomic force microscopy and scanning electron microscopy and the mechanical properties of the lignin-based polyurethane samples were measured using dynamic mechanical analysis and Shore hardness (Type A). The thermal analysis and morphology studies demonstrate that all polyurethanes prepared form a multiphase morphology. In these polyurethanes, better mixing was observed in the wheat straw lignin polyurethane samples leading to higher moduli than in the hardwood lignin and softwood lignin polyurethanes whose morphology was dominated by larger aggregates. Independent of the type of the lignin used, increasing the fraction of lignin increased the rigidity of polyurethane. Among the different types of lignin studied, polyurethane with wheat straw soda lignin exhibited storage moduli 2-fold higher than those of polyurethanes incorporating other lignins. This study also showed that during synthesis all hydroxyl groups in the lignin are not available to react with isocyanates, which alters the number of cross-links formed within the polyurethane and impacts the mechanical properties of the material.